ANALISIS PENGGUNAAN METODE TIKRAR WA TADRIB PADA PEMBELAJARAN MENULIS KALIMAT SEDERHANA BAHASA ARAB - Zahra Afifa (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2023)
Until now, writing problems still occur in learning Arabic. Various difficulties were experienced by students both in terms of linguistics and non-linguistics. This is because writing is the highest skill in learning Arabic. In addition, the factor of differences in educational background is still a problem in learning Arabic. It requires directed learning stages and appropriate learning methods to develop students skills. Then came the Tikrar Wa Tadrib method to make it easier for students to learn Arabic even though they have diverse educational backgrounds. This research aims to describe how the planning, process, and evaluation of learning when using the Tikrar Wa Tadrib method in learning to write simple sentences in Arabic using a qualitative descriptivemethod. The results of this study indicate that teachers carry out lesson planning by making a lesson plan and syllabus. In the process, the activities of reading nazam, repeating material and increasing practice are the main parts of using the Tikrar Wa Tadrib method. Evaluation of the use of these methods is carried out directly. The results of using this method show that 93% of student scores are in the good category and the level of student understanding reaches 75-90%.